Noradrenergic innervation across brain regions is altered by aging and by disease progression in a mouse model of Alzheimer’s disease neuropathology - Nicole M. Hernandez; Manuel Silva-Pérez; Jeannie Chin (PLoS ONE, 2026)
Norepinephrine plays critical roles in modulating arousal and attention, is highly dynamic in awake, behaving individuals, and has anti-inflammatory and neuroprotective actions. Notably, the locus coeruleus (LC), the primary source of norepinephrine in the central nervous system, is among the first brain regions to show pathological alterations in early stages of Alzheimer’s disease (AD). LC neuronal loss and associated reductions in norepinephrine in the brain have therefore been postulated to play a key role in AD pathophysiology. LC neurons and their axons have been studied in several mouse models of AD-related neuropathology to investigate their contribution to brain dysfunction in AD. However, the time course and spatial distribution of alterations in noradrenergic (norepinephrine-containing) LC projections are not fully understood. We therefore evaluated the density of noradrenergic axonal projections in the cortex and across subregions of the hippocampus in transgenic mice expressing mutant human amyloid precursor protein (APP) and in nontransgenic wild-type littermate controls at 2, 6, 12 and 20 months of age. In comparison to age-matched controls, APP mice displayed region-specific alterations in hippocampal noradrenergic fiber density that followed distinct age-related trajectories, along with subtle decreases in cortical noradrenergic fiber density. The alterations in noradrenergic innervation in APP mice were not associated with the extent of amyloid-β (Aβ) plaque load in the hippocampus or cortex and occurred in the absence of neuronal loss or Aβ plaques in the LC. In wild-type mice, there were subtle but robust alterations in noradrenergic fiber density across the brain between 2–20 months of age. These results reveal the presence of spatiotemporally complex alterations in noradrenergic innervation in the brain across both normal aging and disease progression.